The impact of COVID-19 on mental health of nursing in Intensive Care Units: Integrative review (Research, Society and Development, 2023)
The concern with the mental health of nurses is an extremely relevant theme, especially those who work in Intensive Care Units (ICU), which is intended for the care of critically ill patients, thus causing a greater work overload, which became more evident during the pandemic of COVID-19, declared on March 11, 2020. The objective of this paper is to analyze the impact of COVID-19, on the mental health of nursing professionals who worked in this environment. Method: This is a qualitative research, using the integrative review method. Seven scientific articles were analyzed, with publication between 2020 and 2022. Results: After analyzing the articles, it was evident that professionals who worked in the front line during this period had a higher risk of developing mental disorders, such as burnout syndrome, fatigue, depression, frustration, fear and feeling of devaluation. Conclusion: it was possible to observe the scarcity of studies developed on the theme in Brazil, thus influencing negatively the measures of prevention and control of the impact on the mental health of nursing professionals. Therefore, it is recommended the construction of new content that presents methodologies capable of characterizing substantiation, in order to identify collaborative strategies to support the health system, implementing interventions to promote mental health and the well-being of these professionals, especially regarding the professionals who work on the front line, in order to overcome this crisis, as well as possible future pandemics.